Pengaruh Suku Bunga dan Risiko Reksadana Saham terhadap Asset Under Management - Anggara Ardi Nugroho; Djoko Setyadi; Musdalifah Azis (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
The purpose of this study was to determine the effect of SBI to the Assets Under Management (AUM) at the company's mutual fund shares listed on the stock exchange Indonesia (BEI) and to determine the effect Risk Mutual Fund Shares of the Asset Under Management (AUM) at the company's mutual funds listed shares in the Indonesia Stock Exchange (IDX) with the observation period from 2013 to 2015. Variables used in this research is the SBI is calculated by taking the average value in one year and the Risk of Mutual Fund shares calculated using the Standard Deviation. This research carried out during the period of 3 (three) years. The research data is secondary data obtained from the Website Cash (www.kontan.co.id) which provides financial data. Data analysis technique used is the classical assumption test and multiple linear regression. The population in this study is the product Equity Fund is officially listed in the Indonesia Stock Exchange (BEI) in the period 2013 - 2015. The sampling method is determined by using purposive sampling. The results showed that the SBI has no effect on the Significant Assets Under Management (AUM), while the Risk Mutual Fund Shares significant effect on Assets Under Management (AUM).